2020
DOI: 10.1155/2020/8887593
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Effect of Chitosan Nanoparticles as Final Irrigation on the Apical Sealing Ability and Push-Out Bond Strength of Root Canal Obturation

Abstract: Background/Objectives. Root canal irrigation is a crucial stage during root canal treatment since it can affect the root canal obturation; as a result, the success of root canal treatment can be achieved. The objective of this study is to evaluate the effect of 0.5% chitosan nanoparticles as a final irrigation solution with different application times on the apical sealing ability and the bond strength of root canal obturation. Materials and Methods. Fifty-six premolars were used in this study and divided by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
0
10
1
Order By: Relevance
“…Moreover, sealer penetration results were in agreement with Aydın et al (2019) (39) , who concluded that EDTA enhanced sealer penetration that was superior to chitosan nanoparticle penetration. On the other hand, previous researches contradicted this study's findings, which reported that 0.2% chitosan provided the same bond strength as 17% EDTA (26,31,56) and similar sealer penetration at the middle and apical thirds (31) .…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Moreover, sealer penetration results were in agreement with Aydın et al (2019) (39) , who concluded that EDTA enhanced sealer penetration that was superior to chitosan nanoparticle penetration. On the other hand, previous researches contradicted this study's findings, which reported that 0.2% chitosan provided the same bond strength as 17% EDTA (26,31,56) and similar sealer penetration at the middle and apical thirds (31) .…”
Section: Discussioncontrasting
confidence: 76%
“…Interestingly, chitosan nanoparticles (CSNPs) were demonstrated to be effective in eliminating the smear layer when utilized as a chelating agent (25) . However, studies concerning the effect of CSNPs on the adhesion of endodontic sealers to RC walls are limited (26) .…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] The nanoparticle size of CS can increase irrigation fluid flow into dentinal tubules, hence increasing smear layer clearance. [ 17 ] Besides, CS polymer is hydrophilic. Thus, it supports close contact with root canal dentin that enables it to be easily adsorbed by the walls of the root canal and supplied deeper to the dentinal tubules.…”
Section: Discussionmentioning
confidence: 99%
“… 75 On the other hand, a recent study found that conditioning dentine with a chitosan-hydroxyapatite precursor nanocomplex prior to tricalcium silicate sealer application resulted in significantly improved mean sealer penetration into tubules. 73 Coupled with its antimicrobial properties, chitosan nanoparticle solutions appear to be promising contenders for novel irrigants, 62 , 76 although it has been suggested that the prolonged treatment time and contact-dependent nature of chitosan nanoparticle-based irrigants are limitations that warrant further research to overcome. 64 …”
Section: Irrigation Strategiesmentioning
confidence: 99%